2020
DOI: 10.28992/ijsam.v4i1.163
|View full text |Cite
|
Sign up to set email alerts
|

Counterparties’ Influence on an Enterprise’s Social Capital Formation

Abstract: The purpose of this study is to determine the influence of counterparties on the formation of an enterprise’s social capital, which is a component of measuring its value. The size of social capital is the result of the synergistic effect of all its components, namely, trust, social networks, and social norms. In this research study, the components of social capital in an enterprise are estimated to be part of the relationship with the stakeholders of the enterprise, including counterparties. Liquidity and fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The company's social and environmental responsibilities are voluntary organizational mechanisms to emphasize company attention on society and the environment around the company and its interaction with company stakeholders (Lestari et al, 2019). The disclosure of company performance on culture, environment, and the economy is made separately from annual reporting, and this separation helps increasing the level of accountability, responsibility, and transparency of the company on the eye of investors and other stakeholders (Khalil & O'sullivan, 2017;Odoemelam et al, 2020;Zhyhlei et al, 2020). Sustainability report has become a good trend, and every progressive company begins to feel necessary to conduct sustainability reporting to inform their performance on society, environment, and economy to company stakeholders (Bird & Davis-Nozemack, 2018;Nurim & Asmara, 2019;Semuel et al, 2019;Meutia et al, 2020;Permatasari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The company's social and environmental responsibilities are voluntary organizational mechanisms to emphasize company attention on society and the environment around the company and its interaction with company stakeholders (Lestari et al, 2019). The disclosure of company performance on culture, environment, and the economy is made separately from annual reporting, and this separation helps increasing the level of accountability, responsibility, and transparency of the company on the eye of investors and other stakeholders (Khalil & O'sullivan, 2017;Odoemelam et al, 2020;Zhyhlei et al, 2020). Sustainability report has become a good trend, and every progressive company begins to feel necessary to conduct sustainability reporting to inform their performance on society, environment, and economy to company stakeholders (Bird & Davis-Nozemack, 2018;Nurim & Asmara, 2019;Semuel et al, 2019;Meutia et al, 2020;Permatasari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Past Researches have shown that companies are under pressure from stakeholders to meet environmental expectations and demands by implementing CSR (Andrikopoulos & Kriklani, 2013;Usman, 2020;Zhyhlei et al, 2020), as well as in the hotel industry (Brown, 1996;Kirk, 1998;Cheyne & Barnett, 2001). The pressure has resulted in increasing attention to CSR in business practices (Kotler & Lee, 2011).…”
Section: Introductionmentioning
confidence: 99%